Improving students' spatial thinking ability by applying the "blended learning-rigorous mathematical thinking" model in learning - Makmun Hidayat (12 Waiheru, 2022)
This study aims to describe the improvement of students' spatial thinking ability related to Geometry objects in Mathematics subjects after applying the Blended learning-Rigorous mathematical thinking model. This improvement in spatial thinking skills is in order to improve students' ability to solve mathematical problems and other problems in everyday life. This research is a quantitative descriptive research by applying the Control Group Pretest-Posttest Design. The data analyzed were in the form of student learning outcome values related to spatial thinking ability after the BL-RMT model was applied. The data from the study were analyzed by combining the N-Gain Test and the t-Test. The results stated that classes implementing the BL-RMT model showed an increase in KBSp of 0.477 with a moderate N-Gain category. Classes not given treatment showed an increase in KBSp of 0.252 with a low N-Gain category. Furthermore, based on the t-test results on the KBSp test post value of 4.319 with a Sig (2-tailed) value of 0.000 < 0.05, it means that there is a significant difference between the experimental class and the control class. Based on the results of the study, it can be concluded that the application of the BL-RMT model can improve students' spatial thinking ability.